استراتيجيّات الترجمة في قصة ابن يقظان المترجمة إلى الملايويّة: دراسة تحليليّة من منظور نظريّة نيومارك - نور عريسة عطيرة بنت زين الدين
Translation in literature is a complex and interesting process, where a text is rich in nuances, feelings/emotions, and culture as it is transformed into another language without diminishing its original meaning and authenticity. Therefore, this study aims to analyze the translation strategy used in Ibnu Yaqzan's novel in the context of cultural aspects based on Peter Newmark's translation theory (1988). Ibnu Yaqzan's novel, the work of a famous writer in the Arab world, is work rich in cultural elements and special nuances of communication. Descriptive qualitative method is used in this study, with textual content analysis as the main approach. The main focus is to identify Newmark's (1988) translation strategies and cultural elements that influence meaning in the selection of strategies in the target text. The results of the study show that there are seven of Newmark’s (1988) eight strategies used in an effort to analyze and transfer cultural elements from Ibnu Yaqzan's novel into Malay Language, including Word by Word Translation, Literal Translation, Faithful Translation, Semantic Translation, Free Translation, Idiomatic Translation and Communicative Translation. In the context of cultural equivalence, researcher tries to analyze specific cultural elements in the source culture that are maintained in the target culture as closely as possible.